1988
DOI: 10.1093/ajh/1.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Factor in Pregnancy-induced Hypertension and Preeclampsia: Increased Plasma Concentrations Possibly Explaining These Hypovolemic States With Paradoxical Hyporeninism

Abstract: Plasma immunoreactive atrial natriuretic factor 99-126 (ir ANF), plasma volume, plasma renin activity, and plasma aldosterone were measured during pregnancy in 14 normotensive nonpregnant women, 15 normotensive pregnant women, 35 patients with pregnancy-induced hypertension (PIH), and in ten patients with preeclampsia (PE). Repeated measurements were carried out 2 months after delivery in a subgroup of the same patients. The plasma levels of ANF were found to be higher in pregnant normotensive women than in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

1989
1989
1998
1998

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…However, there was a tendency for ANF to be higher in the pregnant women, particularly in the pre‐eclampsia group. Most investigators have found that ANF is increased in normal pregnancy and paradoxically increased further in pre‐eclampsia 16,18 . Thus, it is likely that the increases we have observed in urinary and plasma cyclic GMP concentrations in normal pregnancy can be due, at least partially, to an influence of ANF.…”
Section: Discussionmentioning
confidence: 63%
“…However, there was a tendency for ANF to be higher in the pregnant women, particularly in the pre‐eclampsia group. Most investigators have found that ANF is increased in normal pregnancy and paradoxically increased further in pre‐eclampsia 16,18 . Thus, it is likely that the increases we have observed in urinary and plasma cyclic GMP concentrations in normal pregnancy can be due, at least partially, to an influence of ANF.…”
Section: Discussionmentioning
confidence: 63%
“…Pre-eclampsia is associated with plasma volume reduction, yet most studies have found that plasma ANP is actually increased in pre-eclampsia (Fievet et al 1988;Malee et al 1992). Lowe er al.…”
Section: Atrial Natriuretic Peptide (Anp)mentioning
confidence: 99%
“…ANP is predominantly produced by the atria in response to atrial stretch and other factors, but is also produced at other sites, including the placenta. Pre-eclampsia is associated with plasma volume reduction, yet most studies have found that plasma ANP is actually increased in pre-eclampsia (Fievet et al 1988;Malee et al 1992). Lowe er al.…”
Section: Atrial Natriuretic Peptide (Anp)mentioning
confidence: 99%
“…Da es bei Sill erh6ht ist, scheint ihm eher eine kompensatorische Rolle zur Verhtimng eines zu starken Blutdruckanstiegs zuzukommen. Je h6her der Blutdruck ist, desto mehr ANP wird Zusammenfassend ergibt sich, dab das ANP sicherlich eine wichtige Rolle in der Regulierung yon Blutdruck und -volumen sowohl in der hypertonen Schwangerschaft spielt, was durch mehrere andere Arbeiten best~ifigt werden konnte (2,3). Ob das ANP als prognostischer oder diagnosfischer Faktor benutzt werden kann oder ob sogar therapeutische Anwendungsm6glichkeiten bestehen, mug sich in der Zukunft zeigen.…”
Section: Diskussionunclassified